Cap-and-Trade Climate Policy, Free Allowances, and Price-Regulated Firms - Bruno Lanz; Sebastian Rausch (ETH Zurich, CER-ETH - Center of Economic Research, 2013)
Firms subject to cost-of-service regulation cannot withhold windfall profits associated with free emissions allowances. This paper examines the efficiency and distributional impacts of two approaches to transfer free allowances to consumers: output subsidies and lump-sum payments. We employ an empirically calibrated model of the U.S. economy that features regulated monopolies in the electricity sector and many heterogeneous households. Under a carbon dioxide cap-and-trade policy, we find that using free allowances to subsidize regulated electricity prices increases aggregate welfare costs by 40-80 percent relative to lump-sum transfers. These inefficiencies are disproportionately borne by households in the tails of the income distribution.
Keywords: C61; C68; D58; Q43; Q54; 330; Climate policy; Cap-and-trade; Allowance allocation; Cost-of-service regulation; Electricity Generation; Emissionshandel; Strompreis; Preisregulierung; Elektrizitätswirtschaft; Marktlagengewinn; USA